Development Of Foxp3(+) Regulatory T Cells Is Driven By A c-Rel Enhanceosome - Ruan, Qingguo (2009)
Regulatory T (Treg) cells play essential roles in maintaining immune homeostasis. While Foxp3 expression marks the commitment of progenitors to Treg lineage, how Treg cells are generated during lymphocyte development remains enigmatic. Both NFAT and Smad have been implicated in Foxp3 gene activation, but mice deficient in them are reported to have normal Treg cell numbers. We report here that c-Rel controls the development of Treg cells by promoting the formation of a Foxp3-specific enhanceosome that contains c-Rel, p65, NFAT, Smad, and CREB. Although Smad and CREB first bind to Foxp3 enhancers, they later move to the promoter to form the c-Rel enhanceosome. Consequently, c-Rel-deficient mice have up to ten-fold reductions in Treg cells, and c-Rel-deficient T cells are significantly compromised in Treg differentiation. Thus, Treg development is controlled by a c-Rel enhanceosome, and strategies targeting Rel/NF-κB can be effective for manipulating Treg function.